Academic Motivation and Psychological Needs as Predictors of Suicidal Risk. Issue 2 (6th July 2019) - Lee, Jerin; Chang, Edward C.; Lucas, Abigael G.; Hirsch, Jameson K.
Abstract : This study examined academic motivation and basic psychological needs as predictors of suicidal risk (namely, depressive symptoms and suicidal behaviors) in a sample of 348 college students. Results from regression analyses indicated that academic motivation was a significant predictor of suicidal risk. The inclusion of basic psychological needs significantly augmented the prediction model. The authors discuss implications for considering academic motivation and basic psychological needs in college counseling on the basis of the results.